PENGARUH POSISI DAN UKURAN BUKAAN TERHADAP TINGKAT PENCAHAYAAN ALAMI PADA BANGUNAN RUMAH TINGGAL DENGAN SIMULASI DIALUX - Nugroho, Ardianto; Hambali W, Reza; Gunawan, Ahmad Nur Sheha (Narada : Jurnal Desain dan Seni, 2023)
The element of natural lighting in a building is how an opening can influence how much light enters a room. In a residential home, openings play an important role, not only as an aesthetic element but also have the function of bringing the outside atmosphere into an interior space. The study will utilize Dialux simulation to compare natural lighting values between existing conditions and proposed designs with varying positions and sizes of openings, along with external reflection elements affecting simulation outcomes. The simulation employs consistent external and internal parameters for direct comparison. The aim is to obtain comparable data for informing the final design, crucial for renovation implementation planning to minimize cost and time impacts. The simulation results indicate that vertical openings in corner of the room have lower lighting levels compared to horizontal openings located centrally on the walls.